Enhancer Analysis Unveils Genetic Interactions between TLX and SOX2 in Neural Stem Cells and In Vivo Reprogramming - Islam, Mohammed M. (Stem Cell Reports, 2015)
The orphan nuclear receptor TLX is a master regulator of postnatal neural stem cell (NSC) self-renewal and neurogenesis; however, it remains unclear how TLX expression is precisely regulated in these tissue-specific stem cells. Here, we show that a highly conserved cis-element within the Tlx locus functions to drive gene expression in NSCs. We demonstrate that the transcription factors SOX2 and MYT1 specifically interact with this genomic element to directly regulate Tlx enhancer activity in vivo. Knockdown experiments further reveal that SOX2 dominantly controls endogenous expression of TLX, whereas MYT1 only plays a modulatory role. Importantly, TLX is essential for SOX2-mediated in vivo reprogramming of astrocytes and itself is also sufficient to induce neurogenesis in the adult striatum. Together, these findings unveil functional genetic interactions among transcription factors that are critical to NSCs and in vivo cell reprogramming.